Analisis Minat Belajar Siswa pada pembelajaran Tematik Tema 9 Kelas IVa SDN Cikoko 03 Jakarta - Delia Anindita; Robiatul Munajah (LP. Ma'arif Janggan Magetan, 2022)
This study aims to explain the learning interest of class IVa students at SDN Cikoko 03 Jakarta in thematic learning theme 9 during the covid-19 pandemic. To find out the supporting factors and inhibiting factors of the interest in learning of grade IVa students at SDN Cikoko 03 Jakarta on thematic learning theme 9. Efforts can be made to increase student interest in learning in grade IVa SDN Cikoko 03 Jakarta. The method used by the researcher is a qualitative descriptive method and the subject of the research is the students and teachers of class IVa at SDN Cikoko 03 Jakarta. Data collection techniques that researchers use are interviews, observation and documentation. The validation method in this study is triangulation. The results showed that the learning interest of grade IVa students at SDN Cikoko 03 Jakarta could be said to be good because in the limited face-to-face learning process (PTMT) the teacher carried out two-way interactions with students, giving assignments as evaluations for students. When distance learning (PJJ) the teacher works with parents to find out the learning interest of grade IVa students at SDN Cikoko 03 Jakarta in thematic learning theme 9. Students have enthusiasm and want to know thematic learning theme 9 during distance learning (PJJ) and also learning limited face-to-face (PTMT). Class IVa teachers at SDN Cikoko 03 Jakarta apply fun and varied learning methods so that students have a good interest in learning and to create fun, creative and innovative learning.